Genotype analysis to clarify RhD variants in discrepant samples of Chilean population - Aburto, Andrés; Zapata, Diego; Retamales, Eduardo; Fernández, Jorge; Barra, Gisselle; Peña, Francisca; Cárcamo, Sofía; Saavedra, Nicolás; Sandoval, Cristian; Orellana, Juan; Caamaño, José (Frontiers in Immunology, 2023)
The D antigen variants are classified as weak, partial, and extremely weak (DEL) and can be differentiated using molecular tests. In Chile, the laboratories of local blood centers do not identify variants of the D antigen, referring them for study to the Reference Laboratory of the Public Health Institute of Chile. So, in this work, we talk about the results of the molecular analysis of variants of the D antigen in a group of samples that had different results in the serological classification. In the D antigen classification of the Rh system, 479 samples with serological discrepant results were sent for molecular analysis. The Rh phenotype was performed with monoclonal anti-C, anti-c, anti-E, and anti-e antisera by direct agglutination. To find the D antigen, researchers used direct agglutination with monoclonal antisera and indirect antiglobulin testing with the column (gel) agglutination method. Molecular analysis was performed with a polymerase chain reaction with sequence-specific primers (SSP-PCR) and sequencing. The presence of D antigen variants was confirmed in 332 samples (69.3%), with an initial discrepancy in serological classification. In this group of discrepant samples, the frequency of weak RhD variants was 66% (219/332), that of extremely weak RhD was 28% (93/332), and that of partial RhD was 6% (20/332). The weak variants type 2 (27.4%), type 3 (8.4%), type 48 (8.4%), and type 1 (8.1%) were the next most prevalent variants after RHD*DEL43 (28%). The ccEe (R2r) phenotype was the most frequently detected (38.4%) and is present in 87% of the RHD*DEL43 samples. The E antigen is associated with the presence of this variant. Our analyses give the first description of D antigen variants in Chile. The most common variants are DEL type (RHD*DEL43) and weak (weak type 2), which are linked to the ccDEe (R2r) phenotype. These findings allow us to characterize the variants of the D antigen in Chile and, according to the obtained data, to design strategies for the management of donors, patients, and pregnant women.